Opportunities and trends in the emergence of religious extremism and terrorism in Kazakhstan society (Eurasian Journal of Religious Studies, 2022)
Religious extremism manifests itself mainly in the deterioration of the socio-economic situation of the country, the decline in the living conditions of the population, dissatisfaction of people with the government and its policy, as well as in the presence of moral and psychological factors affecting the life of people. Harmony with ethnic traditions plays an important role in the system of religious education and methods of combating extremism. In the program for the Prevention of religious terrorism and extremism, it is important to determine the relationship between traditions and religious beliefs in the national culture, harmoniously developing relations between the state and religion, secular society, ensuring social stability and internal security. At the beginning of the years of independence of the Republic of Kazakhstan, all the main efforts to strengthen the state were made to increase the economic potential. Due to the fact that the state did not give a clear direction to the people on the issue of religion, the Kazakh people began to get information about religion and religious sermons from representatives of various religious movements. After arriving religious people from outside and firmly settled on their feet, it became clear that religion has no national split and forms a religious cosmopolitan environment in our country, and now, as you know, in the "January events" in Almaty.Keywords: religion, extremism, terrorism, Islamic Civilization, fundamentalism.
Keywords: religion; extremism; terrorism; Islamic Civilization; fundamentalism